Entre lingüística y fenomenología: una mirada crítica a Forma y sustancia en los sonidos del lenguaje de E. Coseriu - Moreno Tirado, Guillermo (2025)
This paper questions the use of the “form/substance” pair in Coseriu’s essay Form and Substance in Language Sounds, from the hermeneutic phenomenological method. I argue that, from a hermeneutic phenomenological point of view, the main argument of Coseriu's contribution makes it unnecessary to recognize the dual ontological dimension of language (nature and mind) that the author maintains in his exposition. I will defend that neither the operability of the pair nor the dual aspect it leads to are consistent, justifying why the use of the pair should be abandoned, the conception of the dual ontological nature of language rejected, and showing the potential that a properly understood method holds for theoretical linguistics and the history of linguistics.